A Feasibility Study on Shell Button Manufacturing - Arellano, Angelo; Buñag, Sylvi; Rivera, Charit (Diliman, Quezon City College of Engineering, 1994)
Buttons are so common in everyday life that most people forget its usefulness. It was the group's concern to find out what was behind the making of these buttons. The Philippines, being a country situated in an archipelago is rich in marine life. This being the case, the group decided to concentrate on seashells as the main source of raw material for making the buttons specially since consumers are willing to pay a premium on authentic shell buttons. In the market study conducted, it was found that there are 9 local manufacturers. Out of all these manufacturers, only a few supply locally. In fact, interviews revealed that almost eight (80) percent shell buttons supplied to the Philippine market are from foreign competitors. The top three suppliers to the Philippines are Hong Kong, Japan, and Taiwan. When it comes to the foreign market, the top six importers of Philippine-made shell buttons were focused on. Namely, USA, Germany, Hong Kong, Japan, Taiwan, and Italy. The market study produced encouraging results and thus, the group decided to continue and do a technical feasibility study. The process of making shell buttons is quite simple and inexpensive. The raw materials, machinery and manpower requirements for the project are available. The technology for producing shell buttons outlined in the study is adequate to produce the quality required by future customers. The company has a two phase production plan. The first phase involves catering to the local market exclusively. In the second phase, the company will expand its market base to the foreign market. The company will begin operations in 1996 at 30% capacity and will reach full capacity by the fourth year of operations. Based on the sales and costs of production that were obtained from the market and technical study, the projected income of the company is conservative in the first two years but is impressive in the long term. Thus this project is feasible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Pearl button industry; Mother-of-pearl.; Shell; Participatory monitoring and evaluation (Project management)